Organizational development differentiating social strategic change “perceptions of the academic community of public academy programs of institutions of higher education” - Romero Palacios, Wilson Eduardo; Jara Vargas, Maria Del Pilar (Universidad Francisco de Paula Santander, 2016)
Accountant of today's organizations, as Goodman and Kurke (1982) assures, “highlight the existence of a common meaning that is presented in the different existing meanings of change, independently, which defines doing something different, which can be changed It may be different, that you can be different, attitudes, beliefs, behavior of individuals, patterns of interaction of roles or groups, organizations, individuals, patterns of interaction of roles or groups, organizations, strategies, change is always the alteration of state to state For this reason this influences the Public Accountancy focused on internationalization, which allows in this research to mention the various concepts that are integrated in the organization, as well as its phases, organizational development process, the importance of criticism of the model of the structure and make analysis of the different models of organizational development and identify the advantages and disadvantages of each one to visualize which is the most convenient to apply in an organization focused on: “Perceptions of the Accounting Academic Community of Higher Education Institutions City Of Santiago De Cali On Organizational Development A Differentiator Of Social Strategic Change. What shows that it is pertinent to analyze the strategic change to channel actions to be implemented in similar situations, even if the contexts are differents.